Genetically modified plants : assessing safety and managing risk - Tzotzos, George T. (Elsevier/Academic Press, 2009)
A transgenic organism is a plant, animal, bacterium, or other living organism that has had a foreign gene added to it by means of genetic engineering. Transgenic plants can arise by natural movement of genes between species, by cross-pollination based hybridization between different plant species (which is a common event in flowering plant evolution), or by laboratory manipulations by artificial insertion of genes from another species. Methods used in traditional breeding that generate transgenic plants by non-recombinant methods are widely familiar to professional plant scientists, and serve important roles in securing a sustainable future for agriculture by protecting crops from pest and helping land and water to be used more efficiently. There is worldwide interest in the biosafety issues related to transgenic crops because of issues such as increased pesticide use, increased crop and weed resistance to pesticides, gene flow to related plant species, negative effects on nontarget organisms, and reduced crop and ecosystem diversity.